Euglycemic diabetic ketoacidosis induced by dapagliflozin in the perioperative period – A case report - Shamshuzoha, M; Chavan, Priyanka; Thamburaj, Jeshwin (Indian Journal of Case Reports, 2024)
Dapagliflozin is a sodium-glucose co-transporter 2 (SGLT2) inhibitor used in the treatment of type 2 diabetes mellitus. SGLT2 inhibitors are known to cause diabetic ketoacidosis (DKA) with normal to mild increases in blood glucose levels. Euglycemic DKA develops in patients with pre-existing risk factors such as major surgery, missed insulin dosage, dehydration, and other acute medical illnesses. We describe a 54-year-old female diabetic patient who developed severe DKA in the post-operative period with normal blood glucose levels presenting as acute abdomen. She was successfully managed with DKA protocol and was discharged from the hospital.